1977
DOI: 10.1097/00004032-197710000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Structure Shielding in Reactor Accidents

Abstract: Radiation shielding provided by transportation vehicles and structures typical of where people live and work were estimated for cloud and fallout gamma-ray sources resulting from a hypothetical reactor accident. Dose reduction factors are recommended for a variety of situations for realistically I assessing the consequences of reactor accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…Table 3 shows the comparison of the shielding factors of the present study with those of the previous works [4][5][6]. Burson et al [4] showed the calculated values of 0.2 or less as the shielding factor for air submersion. The calculations are made for large office or industrial type building without considerations of contributions of windows.…”
Section: Shielding Factors For the Facilitiessupporting
confidence: 54%
See 2 more Smart Citations
“…Table 3 shows the comparison of the shielding factors of the present study with those of the previous works [4][5][6]. Burson et al [4] showed the calculated values of 0.2 or less as the shielding factor for air submersion. The calculations are made for large office or industrial type building without considerations of contributions of windows.…”
Section: Shielding Factors For the Facilitiessupporting
confidence: 54%
“…For the exposures to deposited radionuclides, the shielding factor of 0.05 was proposed by Burson et al [4]. This value is derived experimentally from fallout radiation in the first floor of 3 or 4-story buildings.…”
Section: Shielding Factors For the Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Burson and Profio, 1977). For both kinds of outdoor rural locations, "predominantly unpaved" sites and a mixture over meadows and plowed fields, locations factors fdt) were found to be relatively independent of time after deposition.…”
Section: Average Deposition Conditionsmentioning
confidence: 86%
“…The location factors derived for these cases were based on the data published by Burson and Profio (1977). For single family houses (cases i and ii), corrections were made as the assumed spectrum used in their calculations had a substantial high energy component (above 1 MeV) and experimental results were conducted with a %o source (average energy of 1.25 MeV).…”
Section: Questionmentioning
confidence: 99%